Evidence for the confinement of magnetic monopoles in quantum spin ice. (20th October 2017) - Sarte, P M; Aczel, A A; Ehlers, G; Stock, C; Gaulin, B D; Mauws, C; Stone, M B; Calder, S; Nagler, S E; Hollett, J W; Zhou, H D; Gardner, J S; et al.
Abstract: Magnetic monopoles are hypothesised elementary particles connected by Dirac strings that behave like infinitely thin solenoids (Dirac 1931 Proc. R. Soc . A133 60). Despite decades of searching, free magnetic monopoles and their Dirac strings have eluded experimental detection, although there is substantial evidence for deconfined magnetic monopole quasiparticles in spin ice materials (Castelnovo et al 2008 Nature 326 411). Here we report the detection of a hierarchy of unequally-spaced magnetic excitations via high resolution inelastic neutron spectroscopic measurements on the quantum spin ice candidate P r 2 S n 2 O 7 . These excitations are well-described by a simple model of monopole pairs bound by a linear potential (Coldea et al Science 327 177) with an effective tension of 0.642(8) K ⋅ A ˚ − 1 at 1.65 K. The success of the linear potential model suggests that these low energy magnetic excitations are direct spectroscopic evidence for the confinement of magnetic monopole quasiparticles in the quantum spin ice candidate P r 2 S n 2 O 7 .